Emotional Feelings: Evaluative Perceptions or Position-Takings? Introduction to the Special Section. (October 2022) - Reisenzein, Rainer; Schmidt, Philipp
This special section of Emotion Review is devoted to the discussion of a recent philosophical emotion theory, the theory of emotions as affective position-takings (Jean Moritz Müller, The World-Directedness of Emotional Feeling: On Affect and Intentionalit y, Palgrave MacMillan, 2019). The aims of the special section are to provide readers with a spotlight view of recent research in the philosophy of emotion, to advance emotion theory, and support the interdisciplinary dialogue. To increase the accessibility of the special section texts to a nonphilosophical readership, we first discuss the relationship between the philosophy and the psychology of emotions and give a brief review the main types of theories of emotional experience.